Natural deep eutectic solvent extraction of xanthorrhizol and curcuminoids from Curcuma xanthorrhiza Roxb and simultaneous determination by high-performance liquid chromatography - Adelina Simamora; Kris H. Timotius; Heri Setiawan; Masteria Y. Putra; Abdul Mun’im (Journal of Pharmacy & Pharmacognosy Research, 2023)
Context: Curcuma xanthorrhiza, a native to Indonesia, has been recognized as a potential medicinal plant. Xanthorrhizol (XTZ), curcumin (Cur), bisdemethoxycurcumin (BDMC), and demethoxycurcumin (DMC) are the main major metabolites with different bioactivities. Thus, the selective extraction of these markers is required.